Issues of public education in East Prussia - Endzinas, A. (Psichologija, 1968)
Even before 18th century East Prussia was attempting to expand the network of schools and elevate the level of education. Attempts were made to introduce compulsory education. Schools operating at parish centers (parish schools) and small rural schools included the Lithuanian language lessons in their curricula. The majority of East Prussia rural residents were Lithuanian, and in cities-German; therefore, mainstream teaching in cities was in the German language. In rural schools children were taught to read and sing, later-to write and calculate. Books used for teaching to read were the Bible, Catechism and songbook published in Lithuanian. At the beginning of 18th century, plague exterminated a great number of residents in East Prussia. Its rulers started extensive colonization of the country by Germans. In the first half of 18th century a large number of German colonists were settled in East Prussia. At that period, a network of rural schools designed to teach colonist children expanded. Colonists were not able to adapt to the local conditions and a major part of them left. Therefore, in rural schools the number of local residents’ children increased and their teaching was conducted in Lithuania; furthermore, the East Prussian authority, disappointed in colonists, concentrated on taking better care of local inhabitants of the country. In the second half of 18th century, the colonization proceeded in lesser degree but in a more compact way; therefore, German schools were opened in those places, though they were not numerous. The majority of rural schools were intended to teach local residents-Lithuanian peasants. Lithuanian peasants in East Prussia were called “žemininkai” (“land plot keepers”) and the schools were called accordingly-“žemininkų mokyklos” (“schools for land plot keepers”). Teaching in these schools was conducted in the Lithuanian language and most of their teachers even did not know German. At the end of 18th century and at the beginning of 19th in “land plot keepers’ schools” the transit to the secular content took place which complied to the interests of the rural residents. For that purpose relevant course-books were published in the Lithuanian language.